PENGARUH GAYA KEPEMIMPINAN TRANSAKSIONAL DAN TRANSFORMASIONAL TERHADAP KOMITMEN AFEKTIF MELALUI KEPUASAN KERJA (Studi Empiris pada Petugas Lapangan Badan Pusat Statistik Provinsi Daerah Istimewa Yogyakarta) - Dyah Maryanti (MM UMY, 2015)

(untitled)
This study aimed to analyze the influence of transactional and the transformational leadership style toward the affective commitment of field officers of the Central Bureau of Statistics of Yogyakarta special region through job satisfaction. This research was executed in BPS-Statistics of Regencies/Cities in the Daerah Istimewa Yogyakarta Province with 75 respondent. The respondent in this research is field officer that can call Koordinator Statistik Kecamatan (KSK). Analysis techniques using Structural Equation Modeling (SEM) was used to test the 7 (seven) hypotheses have been developed . Hypothesis testing results show that there are five hypotheses were accepted. Hypotheses are, among others leadership style transactional positive and significant impact on the affective commitment, transformational leadership style positive and significant impact on the affective commitment, leadership style transactional positive and significant impact on job satisfaction, transformational leadership style positive and significant impact on job satisfaction and job satisfaction positive and significant impact on the affective commitment . While the two hypotheses were rejected, among others, the sixth hypothesis is that job satisfaction is not proven mediating influence between transactional leadership styles of affective commitment and seventh hypothesis that job satisfaction is not proven mediating influence between transformational leadership style on affective commitment .